PENERAPAN TEKNIK RELAKSASI NAFAS DALAM (DEEP BREATHING EXERCISE) TERHADAP NYERI PERSALINAN KALA I FASE AKTIF PADA IBU PRIMIPARA - Aulia; Ahmaniyah; Arisda Candra Satriwati; Puput Kurniasari; Aulia Aulia; Ahmaniyah Ahmaniyah (Bajang Institute, 2026)
: The childbirth process is a long-awaited moment, yet it often brings tension and fear for pregnant women. High levels of anxiety can activate the sympathetic nervous system and increase stress hormones such as cortisol and adrenaline, which in turn reduce the production of oxytocin and endorphins—natural hormones that regulate uterine contractions and relieve pain. To help mothers cope with labor pain without disrupting the physiological process of childbirth, various non-pharmacological methods have been developed. One such method is the deep breathing relaxation technique, which functions to balance the autonomic nervous system, improve oxygenation, and reduce muscle tension, thereby decreasing pain perception—particularly among women experiencing childbirth for the first time. Methods: This study employed a quasi-experimental design with a pretest–posttest control group design. The population consisted of 30 participants divided into two groups: 15 in the experimental group and 15 in the control group. Data were collected using the Numerical Rating Scale (NRS) for pain, ranging from 0 to 10. Statistical analysis was performed using the Wilcoxon signed-rank test, and the sampling technique applied was purposive sampling. Results: Statistical testing showed a significance value (p-value) = 0.000 (p < 0.05), indicating that the reduction in pain level after the intervention was statistically significant. This finding demonstrates the effect of the deep breathing technique in reducing labor pain during the active phase of the first stage of labor in primiparous women. Conversely, in the control group that received only position change intervention, the results indicated a tendency toward increased pain intensity, with the mean pain score rising from 4.93 to 5.27, a mean difference of –0.34, and a p-value = 0.055 (p > 0.05).